The Order of Beneficence in Thomas Aquinas - Galewicz, Włodzimierz (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
This paper aims to provide a contribution to the perennial discussion on ranking of our duties to help others by analyzing Thomas Aquinas’s conception of the order of beneficence. After outlining Aquinas’s notion of beneficentia as a virtue guiding positive duties to others I present his prioritization of these duties as a version of multi-criteria approach, developing antecedent ideas of Aristotle and Cicero. In reference to these philosophers, I distinguish a few crucial principles used for priority setting in discharging duties to act for the good of others: the rule of greater commitment, the rule of closer connection, the rule of greater need, the rule of greater benefit and the rule of higher worth. Then I seek to highlight how these principles and their sub-criteria are accounted for and applied by Thomas Aquinas, focusing especially on his considerations how to resolve conflicts among competing rules of preference.